On the town : Midland view four sculpture show : A city wide exhibition of contemproary sculpture. - Coventry Whitefriars, Coventry; Lanchester Gallery, Coventry Polytechnic Faculty of Art and Design, Coventr; Herbert art Gallery and Museum, Coventry; Mead Gallery, Warwick (Coventry : City of Coventry, 1987)
Bevan, Rob ; Crutchley, R.H. ; Cunseath, Chris ; Havers, Mandy ; Nowasielska, Anna ; Saint, Alison ; Coates, Andrw ; Nixon, Julia ; Adams, Stephen ; Bailey, Suzanne ; Berry-Har, David James ; Best, Anna ; Bordonari, Angelo ; Brown, Hilary ; Cobb, Peter ; Cooper, David ; Edmunds, Frank ; Farrell, Michael ; Fletcher, Yan ; Lemon, Liz ; etc.
On the town : Midland view four sculpture show : A city wide exhibition of contemproary sculpture, Coventry Whitefriars, Coventry / Lanchester Gallery, Coventry Polytechnic Faculty of Art and Design, Coventry / Herbert art Gallery and Museum, Coventry, September 12 - October 31 1987 / Mead Gallery, Warwick University Arts Centre, October 3-31, 1987
boek